Complications and early results after operative fixation of 68 pilon fractures of the distal tibia. Issue 2 (May 2015) - Lomax, Adam; Singh, Anjani; Jane Madeley, N; Senthil Kumar, C
Background and aims: In this cohort study, we present comprehensive injury specific and surgical outcome data from one of the largest reported series of pilon fractures of the distal tibia treated in a UK tertiary referral centre. Methods and results: A series of 68 closed pilon fractures were retrospectively reviewed from case notes, plain radiographs and computed tomography imaging. Patient demographics, injury and fracture patterns, methods and timing of fixation and clinical and radiological outcomes were assessed over a mean follow-up period of 7.7 months (1.5–30). Overall, deep infection occurred in 1.6% with superficial infection and wound breakdown occurring in 6.3% of cases. Rates of nonunion and malunion were 7.8%. Radiological posttraumatic arthritis was present in 26.6%, which was symptomatic and requiring orthopaedic management in 9.4%. Further surgery for all causes occurred in 26.6% of cases. Conclusion: Fixation of these complex fractures in subspecialist units can achieve overall low rates of wound complications, with definitive fixation of selected fractures within 48 h of initial presentation achieving comparable results to those fixed in a delayed fashion. However, this injury continues to have a significant overall complication rate with a high chance of developing early posttraumatic arthritis and of requiring further surgery.